PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada PT. Kereta Api Indonesia (Persero) Daop 4 Semarang) - Handoko, Ahmad; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2015)
This research has purpose to analyze the influence of transformational leadership and work motivation on employee performance with job satisfaction as an intervening variable (research in PT. Kereta Api Indonesia (Persero) Daop 4 Semarang).The respondent for this research totaled 100 employees PT. Kereta Api Indonesia (Persero) Daop 4 Semarang. Technique of sample collection used Accidental Sampling and used the analysis of Linear Analysis, Path Analysis and Test Sobel.Research result showed that the transformational leadership has a positive and significant influence on the job satisfaction, work motivation has a positive and significant influence on the job satisfaction, transformational leadership has a positive influence but is not significant on the employee performance, work motivation has a positive influence but is not significant on the employee performance, job satisfaction has a positive and significant influence on employee performance. Additionally, job satisfaction just capable mediating the relationship between work motivation on employee performance.